Asuhan Keperawatan Medikal Bedah Pada Tn.G Dengan Penyakit Unstable Angina Pectori (Uap) Di Ruangan Jantung Rumah Sakit M. Natsir Solok - Stevie Anza Resta; Mike Asmaria; Aulia Asman; Kheniva Diah Anggita (CV. ITTC INDONESIA, 2026)
Unstable Angina Pectoris (UAP) is one of the leading causes of mortality worldwide. Approximately 9.4 million people have been diagnosed with Unstable Angina Pectoris, and more than 7.4 million deaths are reported globally. At M. Natsir Solok Hospital, 1,580 cases of Unstable Angina Pectoris were recorded in 2025, highlighting the need for serious and comprehensive management of this condition. This study aimed to describe the implementation of nursing care for patients with Unstable Angina Pectoris using a case study design and a nursing process approach, including assessment, nursing diagnosis, intervention, implementation, and evaluation. The study was conducted in the Cardiac Ward of M. Natsir Solok Hospital from February 25 to 27. The results of the study on Mrs. G showed that patients with UAP commonly experience chest pain, shortness of breath, and activity intolerance. The nursing diagnoses identified included ineffective breathing pattern, risk for ineffective myocardial perfusion, acute pain, impaired tissue perfusion, and activity intolerance. Nursing interventions provided consisted of monitoring vital signs, administering oxygen therapy, positioning the patient in a semi-Fowler position, providing patient education, and collaborating in the administration of medical therapy. After several days of nursing care, the patient's condition showed improvement, as evidenced by reduced chest pain and increased comfort. The conclusion of this study is that comprehensive and appropriate nursing care can help improve the condition of patients with Unstable Angina Pectoris and prevent further complications. Therefore, nurses play a crucial role in delivering optimal care through a holistic and continuous approach.